Learning to solve problems : an instructional design guide - Jonassen, David H. (San Francisco, CA : Pfeiffer, 2004)
Learning to Solve Problems is a much-needed book that describes models for designing interactive learning environments to support how to learn and solve different kinds of problems. Using a research-based approach, author David H.
Includes bibliographical references
Keywords: Instructional systems -- Design; Problem solving -- Study and teaching